Persepsi Tentang Gelar Karaeng dan Perilaku Keagamaan Di Desa Tolo Kecamatan Kelara Kabupaten Jeneponto - Ratika Nengsi; Andi Fadilah A Natsir (Universitas Muslim Indonesia, 2023)
This study aims to examine and analyze and verify how people are bound by religion and culture, as well as a social position that is sometimes given to the ancestral status, and how religious experiences are carried out by the community in Tolo Village, Jeneponto Regency. The data was obtained through field searches using research methods and instruments which were then collected. As well as, reviewing related references regarding the focus of this research. The description of the results of the research conducted provides information regarding the existence of various public perceptions regarding the awarding of the title of karaeng to someone. Based on that, by looking at history, there has been a transformation of this understanding. Furthermore, matters related to the religious behavior of the community in Tolo Village, Tolo Sub-District, Jeneponto Regency run as is commonplace for religious activities in general in society. However, one thing that is interesting is the permission from the descendants of the karaeng at Masigi'Lompoa (Great Mosque) when routine religious activities are to be carried out. The routine of religious behavior cannot be separated from Islamic teachings as the religion that the majority of the people in Tolo Village adhere to is Islam. Religious behavior that exists in the community is study, recitation, assemblies of taklim, tahsin al qira'ah, although in fact from the results of research, these activities do not really attract the attention of other communities to strengthen their understanding of religion.